Wittgenstein: significado y representaciones - Skidelsky, Liza (Análisis Filosófico, 1999)
In this paper I claim that although second Wittgenstein's conception of meaning has been thought asan attack to thc notion ofrepresentation, i! is compatible with this notion as it is meant in cognitive science. In order to show this, first, 1 reconstruct Wittgenstein's thesis. Second, I detach the representational thesis from the intemalist and epistemological ones. Then I show that the opponents of the wittgensteinian conception of meaning are the last two thesis.